New tertiary amine-derived C2-symmetric chiral pyridine-N, N′-dioxide ligands and their applications in asymmetric catalysis. Issue 24 (4th November 2022) - Liu, Ren-Ming; Wang, Yu-Heng; Chen, Zi-Yue; Zhang, Lei; Shi, Qing-Hui; Zhou, Ying; Tian, You-Ping; Liu, Xiong-Li
Abstract : Developing efficient methods for preparing privileged chiral ligands is an important endeavor in synthetic chemistry. Abstract : Developing efficient methods for preparing privileged chiral ligands is an important endeavor in synthetic chemistry. Herein, we develop an effective, modular method for the synthesis of tertiary amine-derived C 2 -symmetric chiral pyridine- N, N ′-dioxides (Py-2NO) from optically pure l -prolinamides/hydroxylprolinamides in operationally simple two steps and up to 62% overall yield. The key to the preparation of these chiral Py-2NO ligands was the regioselective N -oxidation of their corresponding chiral intermediate bis(pyrroloimidazolone)pyridines with m -CPBA. To the best of our knowledge, our work is the first report showing that the amine oxide is trans to the adjacent carboxyamide in chiral N -oxides and is also an unprecedented example of the synthesis of tertiary amine-derived C 2 -symmetric chiral pyridine- N, N ′-dioxide ligands, expanding the chemical space of chiral N -oxides. The catalytic activity of these novel Py-2NO ligands was evaluated in the asymmetric Friedel–Crafts alkylation reaction of indoles. The desired products were obtained with up to 92% yield and 99% ee with a low loading % of the Py-2NO-Ni(ii ) complex.